1370 The Relationship Between Pregnant Mother's Condition and Neonatal Mortality Rate. (October 2012) - Kosim, MS; Nenden, NA; Saad, B; Farid, AR
Abstract : Background: Neonatal mortality is still a problem around the world. The rate is varies from country to country. Mother's condition was associated with the outcome of conception and mortality rate. Objective: To determine the relationship between mother's condition and neonatal mortality rate. Methods/design: Case control study. Case group was 40 mothers of neonates who died in high risk neonatal ward Dr. Kariadi Hospital Semarang Indonesia within period of January to December 2011 who fulfilled inclusion criteria. Control group was 40 mothers of neonates who survived. Mother's condition that was studied included mother's age, parity, gestational age, antenatal care, mother's infection, diabetic mother, severe anemia, preeclampsia, eclampsia, hypertension, heart disease, and antenatal bleeding. Data was taken from medical records. Statistical analyses used X 2 and logistic regression. Result: Between groups respectively: age >30-year old, has OR 0.70; 95% CI 0.27–1.82). multiparity (OR 1.22; 95% CI 0.51–2.96). preterm, (OR 2.78; 95% CI 1.12–6.89). ANC, (OR 0.87; 95% CI 0.31–2.44). Mother's infection, (OR 0.29; 95% CI 0.05–1.58). diabetic mother, (OR 4.33; 95% CI 0.46–40.61). severe anemic, d (OR 2.29; 95% CI 1.76–2.98). preeclampsia mothers, (OR 0.23; 95% CI 0.02–2.16). eclampsia mothers, (OR 2.71; 95% CI 0.49–14.90). hypertension mothers, (OR 4.33; 95% CI 0.46–40.60). heart disease (OR 2.02; 95% CI 1.62–2.53). antenatal bleeding (OR 2.33; 95% CI 1.78–3.05). Conclussion: Gestational age (preterm), severe anemia, and antenatal bleeding were associated with neonatal mortality, where gestational age as the major risk factor.